Cervical fractures of femoral bone in eldery patients: epidimeology and causative fractures (literature review) - Hurbanova, Tamara; Babalyan, Vladimir; Cherepov, Dmytro; Kalchenko, Andrii (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2017)
Оccurrence, prevalence and treatment of femoral neck fractures among the elderly and senile were analyzed. The structure of a contingent of patients with fractures of the indicated localization is considered. It is shown that 95 % of people the older age group, femoral neck fractures fractures arise due to low-energy injury. However, there is a clear tendency to increase the number of injuries on the background of osteoporosis in the age group of 40–60 years. Geographical differences in frequency of of the proximal femur fracture occurrence on different continents, as well as between different regions which is determined in a certain way by the genetic environmental factors. For example, it is proved the influence of the amount of sunlight on the frequency of fractures often occur in the winter due to vitamin D deficiency and a decrease in neuromuscular coordination. It is shown that female sex is a risk factor for proximal femur fractures: the ratio of a woman/man aged 60– 69 is 9:2. Wherein women have an absolute number of fractures constantly grows with age. Among other reasons that can lead to the emergence of proximal femur fractures are called: a decrease in bone mineral density, a prolonged glucocorticoids administration, low body weight, smoking, alcohol abuse In Ukraine, there is no official statistics on the prevalence of proximal femur fractures, data on the state of medical services to assist such patients are disparate, the medical and social consequences of treatment outcomes by various methods are practically not analyzed. The results of epidemiological studies may become the foundation for the development of a scientifically sound regional program for the prevention and treatment of proximal femur fractures.